2006
DOI: 10.1016/j.jim.2006.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Method for generation of in vivo biotinylated recombinant antibodies by yeast mating

Abstract: We describe here a novel method for generation of yeast-secreted, in vivo biotinylated recombinant antibodies, or biobodies. Biobodies are secreted by diploid yeast resulting from the fusion of two haploid yeast of opposite mating type. One yeast carries a cDNA encoding an antibody recognition sequence fused to an IgA1 hinge and a biotin acceptor site (BCCP) at the C-terminus; the other carries a cDNA encoding an E. Coli biotin ligase (BirA) fused to KEX2 golgi-localization sequences, so that BirA can catalyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
64
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 55 publications
0
64
0
Order By: Relevance
“…In addition to these efforts, we have generated a cost-and time-effective method for generating site-specific in vivo biotinylated recombinant antibodies secreted by yeast (Biobodies 5,95 ). Biobodies have been generated against HE4 95 and mesothelin 96 .…”
Section: Biomarker Discovery For Ovarian Cancer Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these efforts, we have generated a cost-and time-effective method for generating site-specific in vivo biotinylated recombinant antibodies secreted by yeast (Biobodies 5,95 ). Biobodies have been generated against HE4 95 and mesothelin 96 .…”
Section: Biomarker Discovery For Ovarian Cancer Preventionmentioning
confidence: 99%
“…Biobodies have been generated against HE4 95 and mesothelin 96 . We have also demonstrated that this technology can be used reliably in a highly-sensitive bead-based ELISA assay for screening large populations of women for ovarian cancer 5,67 and for serum biomarker discovery 6 .…”
Section: Biomarker Discovery For Ovarian Cancer Preventionmentioning
confidence: 99%
“…The Bb dissociation K s , as measured by surface plasmon resonance sensor, were of K d = 4.8 Â 10 -9 mol/L and K d = 5.1 Â 10 -9 mol/L before and after purification, respectively (8). We also developed and validated anti-mesothelin Bbs of high affinity that could detect both membrane-bound and soluble forms of mesothelin (9).…”
mentioning
confidence: 99%
“…8). Bbs are recombinant antibodies secreted by diploid yeast as HIS-tagged, in vivo biotinylated proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation